Negócios de impacto social e inovação social: contribuições para a revolução da longevidade - Freitas, Fernanda Cardoso Romão (2018)
The Social Impact Business (NIS) is growing in different parts of the world and Social Innovation (IS) emerges as an alternative to create innovative solutions in an inclusive way. There is evidence that Social Innovation can become important to economic and social growth. Such is due to the fact that we are experiencing transformative challenges such as Longevity Revolution, which is occurring in Brazil and in different parts of the world and requires innovative initiatives to meet new needs resulting from this transformation. In the literature review, there were identified some gaps in the field, such as: few empirical studies about Social Impact Business and Social Innovation and inexistence of studies on NIS and IS for the challenge of longevity increase. Then, from this gap and knowing that in the near future a big part of the population will be elder, we come to the question of this research: How can Social Impact Business and Social Innovation propose solutions to overcome the challenge of increasing longevity? The proposal of this research is to illustrate how Social Impact Business and Social Innovations can bring solutions to this challenge. The methodological procedures followed a qualitative and exploratory approach with interviews to obtain of evidence source. The process of data analysis was done with the help of ATLAS.ti software, based on coding technique. The results of this research show that the main challenge of the Longevity Revolution is prejudice. Other fifteen challenges were evidenced in this research. The greatest contribution in social outcome by the companies participating in this research is the possibility of social existence. This social result contributes strongly to two of the four pillars of Active Aging, which are important elements in response to the Longevity Revolution